Komplikace ve spondylochirurgii: prospektivnŕ 13leté sledování neplánovaných revizních operací páteře - Nesnídal, Petr; Štulík, Jan; Štulík, Jan; Kryl, Jan; Vyskočil, Tomáš; Barna, Michal (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2022)
PURPOSE OF THE STUDY Unplanned revision spinal surgeries constitute a complication in the treatment algorithm for the patient, surgeon and the entire treatment team. Any complication leading to an unplanned revision surgery is therefore undesirable. The percentage of complications referred to in publications on this topic focusing on unplanned revision surgeries only varies from 0.7% to 29.8%, with obvious diversity of causes and significant risk factors. The purpose of the submitted paper is to carry out a prospective evaluation of the most serious complications requiring unplanned revision spinal surgeries in the course of 13 years at a single department performing a broad range of spinal surgeries, namely 1300 procedures annually on average. MATERIAL AND METHODS In the period 2006 - 2018, a total of 16872 patients underwent a surgery at our department. During this period, in 556 patients an unplanned revision spinal surgery was performed. In agreement with literature, the patients were categorised by cause for revision: 1/ impaired wound suprafascial (superficial) healing - superficial infection, 2/ impaired wound subfascial (deep) healing - deep infection, 3/ surgical wound hematoma, 4/ deterioration or occurrence of new neurological symptoms, 5/ cerebrospinal fluid leak (liquorrhoea) and 6/ others. The patients operated on for inflammatory diseases of the spine with subsequent infectious complications, primarily treated at another department, and the patients with open spinal injury were excluded from the study. According to these criteria, a cohort of 521 patients was followed up, namely 236 (45.3%) women and 285 (54.7%) men, aged 1 year to 86 years, with the mean age of 55.0 years (median 60 years). Demographic effects, tobacco smoking and comorbidities were followed up in the cohort, together with the effects of surgery, diagnosis, surgical approach and physician. All parameters were statistically evaluated at a p-value below 0.05, including comparison with the control group. RESULTS Of the total number of 16872 operated patients, a group of 521 (3.09%) patients undergoing a revision surgery for complications was analysed in detail. Impaired wound healing - infection (SSI) was found in 199 (1.18%) patients, of whom superficial infection in 124 cases (0.73%) and deep infection in 75 cases (0.44%). Hematoma in a surgical site was detected in 149 (0.88%) patients. In 63 (0.37%) cases, deterioration of the existing neurological finding or occurrence of a new neurological finding were observed, in 68 (0.40%) cases cerebrospinal fluid leak was reported and in 40 (0.24%) cases other complications were identified. As concerns the surgical assistant, the percentage of complications in a board-certified physician is 2.77 (1.14 - 3.29%), in a medical resident it increases to 3.60 (0.00 - 9.38%) (p<0.05). The prevalence of smokers in the group with complications (N=521) was 34.7%. The control group (N=3650) included 30.1% of smokers (p<0.05). The mean age of patients in the group with complications (N=521) was higher, i.e. 55.0 years, with the median age of 60.0 years, than in the primary cohort (N=16872) with the mean age of 49.8 years and the median age of 52.0 years (p<0.05). The mean BMI in the group with complications was (N=521) 27.3, the median BMI was 26.9. In the control group (N=16872), the mean BMI was 27.11, the median BMI was 26.8. In this case the significance (p>0.05) was not confirmed. The complications prevailed strongly in posterior surgical approach, namely in 483 patients (92.7%). As concerns the surgically treated segment, lumber spine dominates with 320 (61.4%) cases. Corticosteroid therapy was used twice as often in women, namely in 13.1% vs. 6.3%. The group of patients with complications (N=521) showed a much higher average length of hospital stay of 12.8 days compared to the average of 4.6 days (N=16872). DISCUSSION In our cohort, the complication rate was 3.09%, of which infections constituted 1.18%, which is in agreement with similarly focused papers. As regards the patient-related factors, in our study the results reported by literature were confirmed with respect to the age, smoking and comorbidities. Moreover, the posterior surgical procedure, lumber spine surgery and presence of a medical resident are essential (p<0.05). No major age difference was observed between women and men (p>0.05). Obesity is one of the key risk factors, especially in infectious complications. In our cohort, a higher BMI did not increase the risk of complications in general (p>0.05). CONCLUSIONS In correlation with current literature, our cohort confirmed a significantly higher risk of complications leading to revision spinal surgery associated with age, smoking, posterior surgical procedure in thoracic or lumber spine, and presence of a medical resident as a surgical assistant. The average length of hospital stay was demonstrably longer in complicated patients, it almost tripled compared to the whole cohort. Contrary to literature, the effect of obesity on the occurrence of complications was not confirmed. Key words: spinal surgery, complications, infection, reoperation, risk factor, hematoma, cerebrospinal fluid leak, screw malposition, smoking, obesity.
Keywords: obezita; únik mozkomíšního moku; Humans; lidé středního věku; Spinal Fusion; následné studie; Female; lidé; reoperace; hematom; Postoperative Complications; Cerebrospinal Fluid Leak; pooperační komplikace; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Obesity; retrospektivní studie; fúze páteře; mužské pohlaví; Hematoma; Reoperation; Follow-Up Studies